The twist of a knife: a novel (Hawthorne, 4,, 2022)
"When the critic who gave his new play scathing reviews is murdered, stabbed in the heart with his ornamental dagger, author Anthony Horowitz is arrested by an old enemy out for revenge and the only man who can help him is his estranged partner in solving crime, Daniel Hawthorne." --

A howl of wolves: a mystery (Sam Clair mysteries, 4,, 2018)
"Whip-smart (Louise Penny) amateur sleuth Samantha Clair returns in the newest mystery from Judith Flanders, the New York Times bestselling and critically acclaimed author of A Murder of Magpies. Sam Clair figures she'll be a good sport and spend a night out at the theater in support of her upstairs neighbors, who have small parts in a play in the West End. Boyfriend (a Scotland Yard detective) and allround good sport Jake Field agrees to tag along to what is apparently an extra bloody play filled with dramatic gory deaths galore. So Sam expects an evening filled with faux fatalities. Until, that is, the curtain opens to the second act revealing a dummy hanging from the rafters, who's been made up to look suspiciously like Campbell Davison, the director of the production. When Sam sees the horrified faces of the actors onstage, she realizes that this is indeed not a dummy, but Davison himself and this death is not part of the show. Now everyone wants to know who killed Campbell Davison? As Sam learns more about the murdered man, she discovers that he wasn't all that well-liked amongst the cast and crew, so the suspect list grows. The show must go on but Sam knows a murderer must be apprehended so she sets out to find out what happened and why. New York Times bestselling author Judith Flanders once again brilliantly fuses mystery with humor in the fourth installment of her critically acclaimed Sam Clair series"--

Gale encyclopedia of American law (Gale virtual reference library, ,, 2011)
Covers today's leading cases, major statutes, legal terms and concepts, notable persons involved with the law, and important documents. Includes topics such as the Americans with Disabilities Act, capital punishment, domestic violence, gay and lesbian rights, physician-assisted suicide and more.
v. 1. A Fortiori , A Mensa et Thoro , A Posteriori , A Priori , AB Initio , Abandonment , Abatement , Abatement of an Action , Abbott, Benjamin Vaughn , Abdication , Abduction , Abernathy, Ralph David , Abet , Abettor , Abeyance , Abiding Conviction , Abington School District V. Schempp , Abjuration , Abode , Abolition , Abortion , Abrams V. United States , Abrogation , Abscond , Absconding Debtor , Absentee , Absentee Voting , Absolute , Absolute Deed , Abstention Doctrine , Abstract , Abstract of Title , Abstraction , Abuse , Abuse Excuse , Abuse of Discretion , Abuse of Power , Abuse of Process , Abusive , Abut , Abzug, Bella Savitsky , Academic Freedom , Academic Year , Academy of Criminal Justice Sciences , Accede , Acceleration , Acceleration Clause , Acceptance , Access , Accession , Accessory , Accident , Accidental Death Benefit , Accidental Killing , Accidental Vein , Accidents of Navigation , Accommodation Endorsement , Accommodation Paper , Accommodation Party , Accompany , Accomplice , Accomplice Witness , Accord , Accord and Satisfaction , Accouchement , Account , Account, Action on , Account Payable , Account Receivable , Account Rendered , Account Stated , Accountant , Accounting , Accredit , Accredited Law School , Accretion , Accrual Basis , Accrue , Accumulated Earnings Tax , Accumulation Trust , Accumulative Judgment , Accumulative Sentence , Accusation , Accusatory Body , Accused , Acknowledgment , Acquiescence , Acquired Immune Deficiency Syndrome , Acquisition Charge , Acquit , Acquittal , Act , Act of God , Action , Action on the Case , Actionable , Actionable per se , Actual Cash Value , Actual Notice , Actuary , Actus Reus , AD Damnum , AD Hoc , AD Hominem , AD Interim , AD Litem , AD Valorem , Adams, John , Adams, John Quincy , Adaptation , Add-On , Addams, Jane , Addict , Additional Extended Coverage , Additional Instructions , Additur , Adduce , Ademption , Adequate , Adequate Remedy at Law , Adhesion Contract , Adjacent , Adjective Law , Adjoining Landowners , Adjourned Term , Adjournment , Adjudge , Adjudication , Adjudicative Facts , Adjunction , Adjuration , Adjust , Adjusted Gross Income , Adjuster , Adjustment Securities , Administer , Administration , Administration, Office of , Administrative Acts , Administrative Adjudication , Administrative Agency , Administrative Board , Administrative Conference of the United States , Administrative Discretion , Administrative Law and Procedure , Administrative Office of the United States Courts , Administrative Procedure Act of 1946 , Administrator , Admiralty and Maritime Law , Admissible , Admission , Admission to the Bar , Admonition , Adopt , Adoption , Adult , Adulteration , Adultery , Advance , Advance Sheets , Advancement , Adversary Proceeding , Adversary System , Adverse Interest , Adverse Possession , Advice and Consent , Advise , Advisement , Advisory Jury , Advisory Opinion , Advocacy , Advocate , Aeronautics , Affidavit , Affiliation Proceeding , Affinity , Affirm , Affirmance , Affirmation , Affirmative Action , Affirmative Defense , Affray , Aforesaid , Aforethought , After-Acquired Property Clause , After-Acquired Title , After-Born Child , Age Discrimination , Age of Consent , Age of Majority , Age of Reason , Age Requirement for Holding Office , Agency , Agent , Aggravated Assault , Aggravation , Aggression , Aggressive Collection , Aggrieved Party , Agreement , Agricultural Law , Agriculture Department , Agriculture Subsidies , Aid and Abet , Aid and Comfort , Aiding the Enemy Acts , Air Pollution , Airlines , Akerman, Amos Tappan , Alaska Boundary Dispute , Albright, Madeleine Korbel , Alcohol , Alcohol, Tobacco, Firearms, and Explosives, Bureau of , Alderman or Alderwoman , Aleatory Contract , Alexander, James , Alias , Alias Writ , Alien and Sedition Acts , Alien Enemy , Alienable , Alienate , Alienation Clause , Alienation of Affection , Aliens , Alimony , Alito, Samuel Anthony, Jr. , All Fours , Allegation , Allege , Allegiance , Allocation , Allocution , Allodial , Allograph , Allonge , Allotment , Allred, Gloria , Alter Ego , Alteration , Alteration of Instruments , Alternative Dispute Resolution , Alternative Relief , Alternative Writ , Ambassadors and Consuls , Amber Alert , Ambiguity , Ambit , Ambulance Chaser , Ambulatory , Amendment , American Association for Justice , American Association of Retired Persons , American Bankers Association , American Bar Association , American Civil Liberties Union , American Farm Bureau Federation , American Federation of Labor-Congress of Industrial Organizations , American Indian Movement , American Israel Public Affairs Committee , American Legion , American Medical Association , Ames, James Barr , Ames, Samuel , Amicable Action , Amicus Curiae , Amistad Mutiny , Amnesty , Amnesty International , Amortization , Amotion , Amount in Controversy , Analogy , Anarchism , Ancient Lights , Ancient Writing , Ancillary , Ancillary Administration , Animal Rights , Animus , Annexation , Annotation , Annual Percentage Rate , Annual Report , Annuity , Annulment , Anon , Answer , Antarctic Treaty of 1959 , Ante , Antecedent Debt , Anthony, Susan Brownell , Anti-Ballistic-Missile Treaty of 1972 , Anti-Defamation League , Anticipation , Anticipatory Repudiation , Antilawyer Movement , Antinomy , Antitrust Law , Apparent , Appeal , Appear , Appearance , Appellant , Appellate , Appellate Advocacy , Appellate Court , Appellee , Appleton, John , Appoint , Appointment, Power of , Apportionment , Appraisal , Appraiser , Appreciation , Apprehension , Apprentice , Appropriation , Approval , Appurtenance , Arbiter , Arbitrage , Arbitrary , Arbitration , Architect , Architect of the Capitol , Arctic, Legal Status of , Arguendo , Argument , Argumentative , Aristotle , Armed Services , Armistice , Arms Control and Disarmament , Arraignment , Array , Arrears , Arrest , Arrest of Judgment , Arrest Warrant , Arrogation , Arson , Art Law , Arthur, Chester Alan , Articles , Articles of Confederation , Articles of Impeachment , Articles of Incorporation , Articles of Organization , Articles of Partnership , Articles of War , Artificial Insemination , Artificial Person , As is , As per , Ashcroft, John David , Ashwander Rules , Asportation , Assassination , Assault , Assault and Battery , Assembly , Assent , Assess , Assessed Valuation , Assessment , Asset , Assign , Assigned Account , Assigned Risk , Assigned Risk Plan , Assignment , Assignment for Benefit of Creditors , Assigns , Assistance, Writ of , Assisted Suicide , Assize, or Assise , Associate Justice , Assumpsit , Assumption , Assumption of Risk , Assured , Asylum , Asylums , At Issue , At Large , At Law , Atkins V. Virginia , Attachment , Attainder , Attempt , Attenuate , Attest , Attestation , Attorn , Attorney-Client Privilege , Attorney , Attorney General , Attorney Misconduct , Attorney's Fees , Attorney's Lien , Auctions , Audi Alteram Partem , Audit , Augustus, John , Austin, John , Authentication , Authorities , Authorize , Automatism , Automobile Searches , Automobiles , Autopsy , Auxiliary , Aver , Averment , Avoidable Consequences , Avoidance , Avowal , Avulsion , Award , Baby M, in re , Back Pay Award , Back to Work Agreement , Backdating , Bacon, Sir Francis , Bad Faith , Badger, George Edmund , Baer, George Frederick , Bail , Bail Bond , Bailee , Bailey, Francis Lee , Bailiff , Bailment , Bailor , Bait and Switch , Baker, Ella Josephine , Baker V., Carr , Balance Sheet , Balancing , Baldwin, Henry , Baldwin, Joseph Glover , Baldwin, Roger Nash , Baldwin, Simeon Eben , Ballinger, William Pitt , Balloon Payment , Banc , Banishment , Bank for International Settlement , Bank of the United States , Banker's Lien , Bankruptcy , Banks and Banking , Banks, Dennis J. , Bar Association , Bar Examination , Barbour, Philip Pendleton , Bargain , Bargaining Agent , Barlow, Francis Channing , Barr, William Pelham , Barratry , Barrister , Barron V. Baltimore , Barter , Base Fee , Base Line , Baseball , Basis , Bastardy Action , Bates, Daisy Lee Gatson , Bates, Edward , Battel , Battered Child/Spouse Syndrome , Battery , Baylor, Robert Emmett Bledsoe., v. 2. Bean, Roy , Beard, Charles Austin , Bearer , Beasley, Mercer , Beccaria, Cesare Bonesano, Marchese Di , Becket, Saint Thomas , Beecher, Henry Ward , Belief , Bell, Derrick Albert, Jr. , Bell, Griffin Boyette , Bell, John , Below , Bench , Bench Trial , Bench Warrant , Beneficial Association , Beneficial Interest , Beneficial Use , Beneficiary , Benefit of Clergy , Benjamin, Judah Philip , Benjamin, Park , Bentham, Jeremy , Bequeath , Bequest , Bering Sea Dispute , Berle, Adolph Augustus, Jr. , Berrien, John Macpherson , Best Evidence , Bestiality , Beyond a Reasonable Doubt , Bias , Bicameral , Bickel, Alexander Mordecai , Biddle, Francis Beverly , Bifurcated Trial , Bigelow, Melville Madison , Bilateral Contract , Bill , Bill of Attainder , Bill of Exchange , Bill of Indictment , Bill of Lading , Bill of Particulars , Bill of Review , Bill of Rights , Bill of Sale , Bills and Notes , Bills of Credit , Binder , Binding Authority , Binding Over , Bingham, John Armor , Binney, Horace , Bird, Rose Elizabeth , Birth Control , Bissell, Wilson Shannon , Black Codes , Black, Hugo Lafayette , Black, Jeremiah Sullivan , Black Letter Law , Black Panther Party , Black Power Movement , Blackacre , Blackford, Isaac Newton , Blacklist , Blackmail , Blackmun, Harry Andrew , Blackstone, Sir William , Blackstone's Commentaries , Blair, John, Jr. , Blank , Blank Endorsement , Blasphemy , Blatchford, Samuel , Block , Blockbusting , Blood Feud , Blotter , Blue Book , Blue Laws , Blue Ribbon Jury , Blue Sky Law , Board of Directors , Board of Pardons , Board of Regents , Body , Body Execution , Boggs, Corinne Claiborne , Boilerplate , Bolin, Jane Matilda , Bona Fide , Bonaparte, Charles Joseph , Bond, Horace Julian , Bonds , Book Value , Booking , Bookkeeping , Bootstrap Doctrine , Borden, Lizzie , Bork, Robert Heron , Bosone, Reva Beck , Boston Massacre Soldiers , Bottomry , Boudinot, Elias , Boundaries , Bounty Hunter , Boy Scouts of America V. Dale , Boycott , Boyle, John , Brackenridge, Henry Marie , Bracket , Bracton, Henry de , Bradford, William (1729-1808) , Bradford, William (1755-95) , Bradley, Joseph P. , Bradwell, Myra Colby , Brady Center to Prevent Gun Violence , Branch Davidian Raid , Brandeis, Louis Dembitz , Breach of Marriage Promise , Breach of the Peace , Breaking , Breckenridge, John , Breese, Sidney , Brennan, William Joseph, Jr. , Brewer, David Josiah , Brewster, Benjamin Harris , Breyer, Stephen Gerald , Bribery , Brickell, Robert Coman , Bridges , Brief , Briggs, Herbert Whittaker , Bright Line Rule , Bring Suit , Broadcasting , Broadhead, James Overton , Broker , Brookings Institution , Brougham, Henry Peter , Brown, Addison , Brown, Henry Billings , Brown, John , Brown, Joseph Emerson , Brown, Ronald Harmon , Brown V. Board of Education of Topeka, Kansas , Brown, Walter Folger , Brownell, Herbert, Jr. , Browning, James Robert , Browning, Orville Hickman , Bryan Treaties , Bryan, William Jennings , Bryant, William Benson , Bryce, James , Buchanan, James , Buchanan, Patrick Joseph , Buck V. Bell , Buggery , Building and Loan Association , Building Codes , Building Line , Building Officials and Code Administrators International , Bulk Transfer , Bulletin , Burden of going Forward , Burden of Persuasion , Burden of Pleading , Burden of Proof , Bureaucracy , Burger, Warren Earl , Burglary , Burke, Edmund , Burlamaqui, Jean Jacques , Burnet, David Gouverneur , Burr, Aaron , Burton, Harold Hitz , Bush, George Herbert Walker , Bush, George Walker , Bush V. Gore , Business Affected with a Public Interest , Business Closings , Business Judgment Rule , Business Record Exception , Business Roundtable , Business Trust , "But for" Rule , Butler, Benjamin Franklin (1795-1858) , Butler, Benjamin Franklin (1818-93) , Butler, Charles Henry , Butler, Pierce , Bylaws , Byrnes, James Francis , C-SPAN , Cabinet , Cable Television , Cahn, Edmond Nathaniel , Calendar , Calhoun, John Caldwell , Call , Calvo Clause , Calvo Doctrine , Camera , Cameras in Court , Campbell, Ben Nighthorse , Campbell, John , Campbell, John Archibald , Campbell, William Joseph , Canada and the United States , Canals , Cancellation of an Instrument , Canon Law , Canon Law Society of America , Canons of Construction , Canons of Ethics , Capacity , Capias , Capital Asset , Capital Punishment , Capital Stock , Capitalize , Capitation Tax , Caption , Cardozo, Benjamin Nathan , Care , Carjacking , Carmichael, Stokely , Carnal Knowledge , Carpenter, Matthew Hale , Carpetbag Judges , Carriers , Carrier's Lien , Carrington, Edward Codrington , Carrington Report , Carry-Back , Carry-Over , Carrying Charges , Carswell, George Harrold , Cartel , Carter, James Coolidge , Carter, James Earl, Jr. , Carter, Robert Lee , Carter, Thomas Henry , Case , Case Agreed on , Case in Chief , Case Law , Case Method , Case or Controversy , Case Stated , Casebook , Casement Sir, Roger David , Casey, William Joseph , Cash Basis , Cash Surrender Value , Casual , Casual Ejector , Casualty , Casus Belli , Categorical , Caton, John Dean , Catron, John , Causa Mortis , Cause , Cause Célèbre , Cause of Action , Caveat , Caveat Emptor , Cease and Desist Order , Cede , Celebration of Marriage , Celia, a Slave , Cemeteries , Censorship , Censure , Census , Center for Constitutional Rights , Centers for Law and Legal Studies , Centers for Medicare & Medicaid Services , Central Intelligence Agency , Century Digest® , Certificate , Certificate of Deposit , Certificate of Occupancy , Certification Proceeding , Certified Check , Certified Copy , Certiorari , Cession , Cestui Que , CF. , C.F. & I. , Chafee, Zechariah, Jr. , Chain of Custody , Chain of Title , Chain Referral , Chambers , Chamizal Tract , Champerty and Maintenance , Chancellor , Chancery , Character Evidence , Charge-Off , Charge , Charitable Trust , Charities , Charles River Bridge V. Warren Bridge , Charter , Chase, Salmon Portland , Chase, Samuel , Chattel , Chattel Mortgage , Chattel Paper , Chávez, César Estrada , Check , Checkoff , Cherokee Cases , Chessman, Caryl , Chicago Eight , Chicago Jury Project , Chicago School , Chief Justice , Child Abuse , Child Care , Child Custody , Child Labor Laws , Child Molestation , Child Pornography , Child Support , Children's Defense Fund , Children's Rights , Chilling Effect Doctrine , Chinese Exclusion Act of 1882 , Chipman, Daniel , Chisholm, Shirley Anita St. Hill , Chisholm V. Georgia , Choate , Choate, Joseph Hodges , Choate, Rufus , Chose , Chose in Action , Christian Coalition , Christian Legal Society , Churning , Circuit , Circuit Court , Circumstantial Evidence , Citation , Citator , Cite , Citizens , Citizens for Decency Through Law , Civil Action , Civil Death , Civil Disobedience , Civil Law , Civil Procedure , Civil Rights , Civil Rights Acts , Civil Rights Cases , Civil Rights Movement , Civil Service , Civil War , Civiletti, Benjamin Richard , Civilian Review Boards , C.J., , Cjs© , Claim , Claim for Relief , Clarendon, Constitutions of , Clark, Marcia Rachel , Clark, Tom Campbell , Clark, William Ramsey , Clarke, John Hessin , Class Action , Clause , Clause Paramount , Clay, Henry , Clayton Act , Clayton, Henry Delamar , Clayton, John Middleton , Clean Air Act , Clean Water Act , Clear , Clear and Convincing Proof , Clear and Present Danger , Clear Title , Cleaver, Leroy Eldridge , Clemency , Clergy Malpractice , Clerical Error , Clerk , Cleveland, Stephen Grover , Client , Client Security Funds , Clifford, Clark Mcadams , Clifford, Nathan , Clinton, Hillary Rodham , Clinton, William Jefferson , Close , Close Writ , Closed Account , Closed Corporation , Closed Shop , Closely Held , Closing , Closing Argument , Cloture , Cloud on Title , Club , Co , Cobb, Thomas Reade Rootes , Cochran, Johnnie L., Jr. , Cockburn, Sir Alexander James Edmund , Code , Code of Federal Regulations , Code of Hammurabi , Code of Judicial Conduct , Code Pleading , Codicil , Codification , Coercion , Cognizable , Cognizance , Cognovit Actionem , Cognovit Note , Cohabitation , Cohen, Felix Solomon , Cohen, Morris Raphael , Cohn, Roy Marcus , Coinsurance , Cointelpro , Coke, Sir Edward , Coke, Richard , Cold War , Collateral , Collateral Attack , Collateral Estoppel , Collateral Heir , Collateral Warranty , Collective Bargaining , Collective Bargaining Agreement , Colleges and Universities , Collier, William Miller , Collision , Collusion , Color , Color of Law , Color of Office , Color of Title , Colorable., v. 3. Co-Maker , Combination , Combination in Restraint of Trade , Comity , Commerce , Commerce Clause , Commerce Department , Commerce, Electronic , Commercial Code , Commercial Law , Commercial Law League of America , Commercial Paper , Commingling , Commission on Civil Rights , Commissioner , Commissioners on Uniform Laws , Commitment , Commitment Fee , Committee , Commodity , Commodity Credit Corporation , Commodity Futures Trading Commission , Common , Common Carrier , Common Council , Common Count , Common Disaster , Common Lands , Common Law , Common-Law Action , Common-Law Courts , Common-Law Marriage , Common-Law Pleading , Common-Law Trust , Common Pleas , Common Scold , Common Stock , Communis Error Facit Jus , Communism , Communist Party Cases , Communist Party USA , Community-Oriented Policing , Community Property , Community Service , Community Services, Office of , Commutation , Compact , Compact Clause , Company , Comparable Worth , Comparative Rectitude , Compensation , Compensatory Damages , Competent , Competent Evidence , Complainant , Complaint , Compliance , Composition with Creditors , Compound Interest , Compounding a Felony , Compounding Offense , Comprise , Compromise and Settlement , Compromise of 1850 , Comptroller , Compulsory Process , Compurgator , Computer-Assisted Legal Research , Computer Crime , Comstock, George Franklin , Comstock Law of 1873 , Con , Concealment of Birth or Death , Conciliation , Conciliation, International , Conclusion of Law , Conclusive , Concur , Concurrent , Concurrent Estates , Concurrent Jurisdiction , Concurrent Resolution , Concurrent Writs , Condemn , Condemnation , Condition , Conditional , Condominium, International , Condominiums and Cooperatives , Condonation , Confederacy , Confederate Attorneys General , Confederate States of America , Confederation , Conference of Chief Justices , Conference of State Court Administrators , Conference on Personal Finance Law , Confession , Confession and Avoidance , Confession of Judgment , Confidential Communication , Confidential Relation , Confiscate , Conflict of Interest , Conformed Copy , Conforming Use , Confrontation , Confusion , Confusion of Goods , Conglomerate , Congress of the United States , Congressional Budget Office , Congressional-Executive Agreement , Congressional Record , Congressional Research Service , Conjugal , Conkling, Roscoe , Connecting Up Doctrine , Connivance , Conquest , Consanguinity , Conscientious Objector , Conscription , Consensual Alteration , Consent , Consent Decree , Consequential Damages , Conservator of the Peace , Consideration , Consignment , Consortium , Consortium/Intergovernmental Corporations and Consortiums , Conspiracy , Constable , Constitute , Constitution , Constitution of the United States , Constitution Party , Constitutional , Constitutional Amendment , Constitutional Law , Construction , Constructive , Constructive Desertion , Constructive Eviction , Constructive Trust , Consular Court , Consular Law Society , Consuls , Consumer , Consumer Credit , Consumer Credit Protection Act , Consumer Fraud , Consumer Price Index , Consumer Product Safety Commission , Consumer Protection , Consumer Software Piracy , Consummate , Contemner , Contemplation of Death , Contempt , Contest , Context , Continental Congress , Contingent , Contingent Fee , Continuance , Continuing Legal Education , Contra , Contraband , Contract with America , Contracts , Contravention , Contributing to the Delinquency of a Minor , Contribution , Controller , Controversy , Controvert , Contumacy , Convention , Conventional , Conventional Forces in Europe Treaty , Conversion , Conveyance , Convict , Conviction , Cooley, Thomas McIntyre , Coolidge, Calvin , Cooling-Off Period , Cooperative , Copyright , Copyright Arbitration Royalty Panel , Copyright, International , Copyright Royalty Tribunal , Copyright Society of the U.S.A. , Coram , Coram Nobis , Coram Rege , Corbin, Arthur Linton , Corespondent , Corner , Corollary , Coroner , Corporal Punishment , Corporate , Corporate Fraud , Corporate Personality , Corporations , Corporeal , Corpse , Corpus , Corpus Delicti , Corpus Juris , Corpus Juris Civilis , Correlative , Correspondence Audit , Correspondent , Corroborate , Corruption of Blood , Corwin, Edward Samuel , Cosigner , Costs , Council , Counsel , Counsellor , Count , Counterclaim , Counterclaims and Setoffs Against Sovereigns , Counterfeit , Counterfeiting , Counteroffer , Countersign , County , Coupon , Course of Dealing , Course of Employment , Course of Performance , Court , Court Administrator , Court Commissioners , Court Hand , Court-Martial , Court of Appeal , Court of Claims , Court of Probate , Court Opinion., Court Reporter , Courtroom Television Network , Courts of Request , Covenant , Covenant, Action of , Covenant Marriage , Cover , Coverage , Coverture , Cox, Archibald , CPA , Craft Union , Cranch, William , Credibility , Credit , Credit Bureau , Crédit Mobilier Scandal , Credit Union , Creditor , Creditor's Bill , Crime Control Acts , Crimes , Criminal , Criminal Action , Criminal Conversation , Criminal Forfeiture , Criminal Law , Criminal Negligence , Criminal Procedure , Criminology , Critical Legal Studies , Crittenden, John Jordan , Crockett, George William, Jr. , Crop Insurance , Crops , Cross-Action , Cross-Claim , Cross-Complaint , Cross-Demand , Cross-Examination , Cruel and Inhuman Treatment , Cruel and Unusual Punishment , Cruelty , CTA , Cuban Missile Crisis , Culpa , Culpable , Culprit , Cum Testamento Annexo , Cummings, Homer Stille , Cumulative Evidence , Cumulative Sentence , Cumulative Voting , Cunnilingus , Cure , Curfew , Curia , Curia Regis , Current Account , Curtesy , Curtilage , Curtis, Benjamin Robbins , Cushing, Caleb , Cushing, Luther Stearns , Cushing, William , Custodial Interrogation , Custody , Customs Duties , Cy Pres , Dallas, Alexander James , Dallas, George Mifflin , Damages , Damnum , Dana, Richard Henry , Danelage , Dangerous Instrumentality , Daniel, Peter Vivian , Darrow, Clarence Seward , Daubert Test , Daugherty, Harry Micajah , Davis-Bacon Act , Davis, Angela Yvonne , Davis, David , Davis, John Chandler Bancroft , Davis, John William , Day Certain , Day in Court , Day, William Rufus , Days of Grace , De Bonis Non Administratis , De Facto , De Jure , De Minimis , De Novo , Dead Man's Statutes , Deadly Force , Death and Dying , Death Warrant , Debenture , Debit , Debs, Eugene V. , Debt , Debt, Action of , Debt Poolers , Debtor , Decalogue Society of Lawyers , Decedent , Deceit , Decennial Digest® , Decision , Decision on the Merits , Declaration , Declaration of Independence , Declaration of Trust , Declaratory Judgment , Decree , Dedication , Deductible , Deduction , Deed , Deed of Trust , Deem , Defalcation , Defamation , Default , Default Judgment , Defeasance Clause , Defeasible , Defect , Defendant , Defense , Defense Department , Defense of Marriage Act of 1996 , Defense Research Institute , Deficiency , Deficiency Judgment , Deficit , Definitive , Deforcement , Defraud , Degree , Del Credere , Delectus Personae , Delegate , Delegation , Deliberate , Delictum , Delivery , Demand , Demeanor , Demise , Democratic-Republican Party , Democratic Party , Demonstrative Evidence , Demonstrative Legacy , Demur , Demurrage , Demurrer , Deny , Dependent , Dependent Relative Revocation , Dependent States , Depletion Allowance , Deponent , Deportation , Depose , Deposition , Depository , Deposits in Court , Depreciation , Deputy , Derivative Action , Derivative Evidence , Derivatives , Derogation , Dershowitz, Alan Morton , Descent , Descent and Distribution , Descriptive Word Index , Desertion , Desk Audit , Destroy , Desuetude , Detainer , Detectives , Detention , Determinable , Determinate Sentence , Determination , Deterrence , Detinue , Detriment , Devens, Charles , Deviance , Devise , Dewey Decimal System , Dewey, Thomas Edmund , Dickinson, John , Dicta , Dictum , Digest , Dilatory , Dilatory Plea , Diligence , Diminished Capacity , Diminution , Diplomatic Agents , Diplomatic Immunity , Direct , Direct Evidence , Direct Examination , Direct Tax , Directed Verdict , Director , Directory , Disability , Disability Discrimination , Disaffirm , Disallow , Disaster Relief , Disbar , Discharge , Disciplinary Rules , Disclaimer , Discontinuance , Discovery , Discretion in Decision Making , Discretionary Trust , Discrimination , Disfranchisement , Dishonor , Disinherit , Disinterested , Dismissal , Disorderly Conduct , Disorderly House , Disparagement , Disparate Impact , Disposable Earnings , Disposition , Dispositive Fact , Dispossession , Dispute , Disqualify , Dissent , Dissolution , Dissolve , Distinguish , Distrain , Distress , Distributee , Distributor , District , District and Prosecuting Attorneys , District Court , District of Columbia , District of Columbia v. Heller , Disturbance of Public Meetings , Disturbance of the Peace , Divers , Diversion , Diversity of Citizenship , Divest , Dividend , Divine Right of Kings , Divorce , Dix, Dorothea Lynde , Dixon, Julian Carey , DNA Evidence , Dock , Docket , Doctrine , Doctrine of Equality of States , Document , Document of Title , Documentary Evidence , Doe, Charles , Doing Business , Dole, Robert Joseph , Dole, Sanford Ballard , Domain , Dombec , Domesday Book , Domestic , Domestic Partnership Law , Domestic Violence , Domiciliary Administration , Dominant , Dominant Cause , Dominion , Donative , Donee , Donor , Doom , Dormant , Dorr, Thomas Wilson., v. 4. Double Entry , Double Indemnity , Double Insurance , Double Jeopardy , Double Taxation Agreements , Doubt , Douglas, Stephen Arnold , Douglas, William Orville , Douglass, Frederick , Dower , Down Payment , Draconian Laws , Draft , Drafter , Drain , Dramshop Acts , Draw , Drawee , Drawer , Dred Scott V. Sandford , Droit , Drug Courts , Drug Enforcement Administration , Druggist , Drugs and Narcotics , Drunkard , Drunkenness , Du Bois, William Edward Burghardt , Dual Nationality , Duces Tecum , Due , Due Date , Due Notice , Due Process of Law , Dueling , Dulles, John Foster , Dummy , Duress , Durham Rule , Duty , Duty of Tonnage , Duvall, Gabriel , DWI , Dworkin, Andrea , Dworkin, Ronald Myles , Dyer Act , Dying Declaration , Earl Warren Legal Training Program , Earned Income , Earnest Money , Easement , Eastman, Crystal , Eaton, Dorman Bridgman , Ecclesiastical Courts , Economic Bailout , Edelman, Marian Wright , Edict , Education Department , Education Law , Effect , Effective Rate , Efficient Cause , E.G. , Eighteenth Amendment , Eighth Amendment , Eisenhower, Dwight David , Ejectment , Elder Law , Election Campaign Financing , Election of Remedies , Elections , Elective Share , Elector , Electoral College , Electricity , Electronic Frontier Foundation , Electronic Surveillance , Element , Eleventh Amendment , Ellis, George Washington , Ellsworth, Oliver , E-Mail , Emancipation , Emancipation Proclamation , Embargo , Embargo Act , Embezzlement , Emblements , Embracery , Emergency Doctrine , Emigration , Eminent Domain , Emolument , Employee Retirement Income Security Act , Employers' Liability Acts , Employment at Will , Employment Law , En Banc , Enabling Clause , Enabling Statute , Enact , Encroachment , Encumber , Encumbrance , Endangered Species Act , Endorse , Endorsement , Endowment , Enemy Combatant , Energy , Energy Department , Enfeoffment , Enfranchisement , Engage , Engagement , Engel V. Vitale , English Law , English-Only Laws , Engross , Engrossed Bill , Enhancement , Enjoin , Enjoyment , Enoch Arden Doctrine , Enrolled Bill , Entail , Enter , Entertainment Law , Entice , Entirety , Entitlement , Entity , Entrapment , Entry , Entry of Judgment , Enumerated , Environmental Law , Environmental Protection Agency , Equal Employment Opportunity Commission , Equal Pay Act of 1963 , Equal Protection , Equal Rights Amendment , Equitable Remedy , Equity , Equity of Redemption , Ergo , Erie Railroad Co. V. Tompkins , Erratum , Error , Ervin, Samuel James, Jr. , Escalator Clause , Escape , Escheat , Escobedo V. Illinois , Escrow , Espionage , Espionage Act of 1917 , Esq , Essex Junto , Establish , Estate , Estate and Gift Taxes , Estimated Tax , Estoppel , Et Al , Et Seq , Ethics in Government Act of 1978 , Ethics, Legal , Ettelbrick, Paula Louise , Euthanasia , Evarts, William Maxwell , Evers, Medgar Wiley , Evers-Williams, Myrlie , Eviction , Evidence , Ex Dividend , Ex Officio , Ex Parte , Ex Post Facto Laws , Examination , Examiner , Exception , Exchange , Exchange of Property , Excise , Exclusionary Clause , Exclusionary Rule , Exclusive , Exclusive Agency , Exculpate , Excuse , Execute , Execution , Executive Branch , Executive Order , Executive Privilege , Executors and Administrators , Executory , Exemplification , Exercise , Exhaustion of Remedies , Exhibit , Exoneration , Expatriation , Expectancy , Expert Testimony , Explosives , Export-Import Bank of the United States , Expository Statute , Express , Expropriation , Expunge , Extension , Extenuating Circumstances , Extinguishment , Extort , Extortion , Extra , Extradition , Extrajudicial , Extraordinary Remedy , Extraterritoriality , Extremis , Extrinsic Evidence , Eyewitness , Face , Face Value , Facsimile , Fact , Fact and Law , Fact Situation , Factor , Factors , Factum , Failure of Consideration , Failure of Issue , Failure to State a Claim , Fair Comment , Fair Credit Reporting Act , Fair Hearing , Fair Housing Act of 1968 , Fair Labor Standards Act , Fair Market Value , Fair-Trade Laws , Fairness Doctrine , False Advertising , False Arrest , False Demonstration , False Imprisonment , False Personation , False Pretenses , Family Car Doctrine , Family Law , Family Medical Leave , Farm Credit Administration , Fatal , Fault , Feasance , Federal , Federal Appendix , Federal Aviation Administration , Federal Bank Acts , Federal Bar Association , Federal Budget , Federal Bureau of Investigation , Federal Communications Commission , Federal Courts , Federal Deposit Insurance Corporation , Federal Election Commission , Federal Emergency Management Agency , Federal Judicial Center , Federal Maritime Commission , Federal Mediation and Conciliation Service , Federal National Mortgage Association , Federal Question , Federal Register , Federal Reporter® , Federal Reserve Board , Federal Rules Decision® , Federal Rules of Evidence , Federal Supplement® , Federal Tort Claims Act , Federal Trade Commission , Federal Unemployment Compensation Act , Federalism , Federalist Papers , Federalist Party , Federation , Fee , Fee Simple , Fee Tail , Fellatio , Fellow-Servant Rule , Felon , Felonious , Felony , Felony-Murder Rule , Feminist Jurisprudence , Fences , Fenwick, Millicent Vernon Hammond , Feoffment , Ferae Naturae , Feres Doctrine , Ferraro, Geraldine Anne , Ferry , Fetal Rights , Fetal Tissue Research , Feudalism , Fiat , F.I.C.A. , Fiction , Fictitious , Fidelity Bond , Fidelity Insurance , Fiduciary , Field Audit , Field Code of New York , Field, David Dudley , Field, Stephen Johnson , Fieri Facias , FIFO , Fifteenth Amendment , Fifth Amendment , File , Filiation Proceeding , Filibuster , Filius Nullius , Fillmore, Millard , Final Decision , Finance Charge , Financial Responsibility Acts , Financial Statement , Finder , Finding , Finding Lost Goods , Fines , Fingerprints , Fire , Fire Statute , Firm Offer , First Amendment , First Impression , First Instance , Fiscal , Fish and Fishing , Fishing Expedition , Fishing Vessels , Fixed Asset , Fixed Charges , Fixture , Flag , Flag Salute Cases , Flagrante Delicto , Fletcher V. Peck , Floating Capital , Floating Lien , Flotsam , F.O.B. , Follow , Foltz, Clara Shortridge , Food and Drug Administration , Footnote 4 , Forbearance , Force , Force Majeure , Forced Sale , Forcible Detainer , Forcible Entry and Detainer , Ford, Gerald Rudolph , Foreclosure , Foreign , Foreign Affairs Power , Foreign Intelligence Surveillance Court of Review , Forensic , Forensic Accounting , Forensic Science , Foreseeability , Forfeit , Forfeiture , Forgery , Form , Formal Party , Formed Design , Forms of Action , Fornication , Forswear , Fortas, Abe , Forthwith , Forum , Forwarding Fee , Foundation , Four Corners , Fourteenth Amendment , Fourth Amendment , Franchise , Frank, Jerome New , Frankfurter, Felix , Franklin, Benjamin , Fraud , Fraudulent , Fraudulent Conveyance , Free Agency , Free Soil Party , Freedom of Association and Assembly , Freedom of Information Act , Freedom of Speech , Freedom of The Press , Freehold , Freight , Freight Forwarder , Freund, Ernst., v. 5. Friedan, Betty Naomi Goldstein , Friend of the Court , Friendly Fire , Friendly, Henry Jacob , Friendly Suit , Fries's Rebellion , Frisk , Frivolous , Frolic , Frontiero V. Richardson , Fruit of the Poisonous Tree , Frustration , Fugitive from Justice , Fugitive Slave Act of 1850 , Fulbright, James William , Full Faith and Credit Clause , Fuller, Melville Weston , Fund , Fundamental Law , Fundamental Right , Fungible , Furman V. Georgia , Future Acquired Property , Future Earnings , Future Interest , Futures , Gag Order , Gag Rule , Game , Gaming , Gandhi, Mohandas Karamchand , Gangs , Gaol , Garfield, James Abram , Garland, Augustus Hill , Garnishee , Garnishment , Garrison, William Lloyd , Garvey, Marcus Moziah , Gas , Gault, in Re , Gay and Lesbian Rights , General Accounting Office , General Agreement on Tariffs and Trade , General Appearance , General Average Loss , General Creditor , General Execution , General Intent , General Jurisdiction , General Legacy , General Services Administration , General Term , General Verdict , General Warranty Deed , General Welfare , Generally Accepted Accounting Principles , Genetic Engineering , Genetic Screening , Geneva Conventions, 1949 , Genocide , Gentlemen's Agreement , Gerrymander , Gi Bill , Gibbons V. Ogden , Gideon V. Wainwright , Gift , Gifts to Minors Act , Gignoux, Edward Thaxter , Gilbert, Cass , Gillett, Emma Melinda , Gilpin, Henry Dilworth , Gingrich, Newton Leroy , Ginsburg, Douglas Howard , Ginsburg, Ruth Bader , Gitlow V. New York , Glanvill, Ranulf , Glass-Steagall Act , Glass, Carter , Gleaning , Gloss , Going Concern Value , Going Public , Goldberg, Arthur Joseph , Golden Parachute , Goldman, Emma , Goldwater, Barry Morris , Gompers, Samuel , Gonzales, Alberto R. , Good Behavior , Good Cause , Good Faith , Good Samaritan Doctrine , Good Time , Good Will , Goods , Gore, Albert Arnold, Jr. , Government Instrumentality Doctrine , Government National Mortgage Association , Government Printing Office , Grab Law , Grace Period , Graduated Tax , Graft , Grand Jury , Grand Larceny , Grandfather Clause , Granger Movement , Grant , Grant, Ulysses Simpson , Grantee , Granting Clause , Grantor-Grantee Index , Grantor , Gratuitous , Gratuitous Licensee , Gratuity , Gratz V. Bollinger , Gravamen , Gray, Horace , Gray, John Chipman , Gray Panthers , Gray, William Herbert, III , Great Society , Green Card , Green Party , Greenberg, Jack , Greenmail , Gregg V. Georgia , Gregory, Thomas Watt , Grier, Robert Cooper , Grievance Procedure , Griggs, John William , Griswold V. Connecticut , Groesbeck, William Slocomb , Gross , Gross Estate , Gross Income , Gross Negligence , Grotius, Hugo , Ground Rent , Grounds , Group Legal Services , Grundy, Felix , Grutter V. Bollinger , Guarantee , Guaranty , Guaranty Clause , Guardian , Guardian Ad Litem , Guardian and Ward , Guest Statutes , Guilty , Gun Control , Habeas Corpus , Habeas Corpus Act , Habendum Clause , Habitability , Habitual , Hague Tribunal , Hamer, Fannie lou Townsend , Hamilton, Alexander , Hammer V. Dagenhart , Hand, Billings Learned , Harbor , Harding, George , Harding, Warren Gamaliel , Harlan, John Marshall , Harlan, John Marshall, II , Harmless Error , Harmon, Judson , Harrison, Benjamin , Harrison, Robert Hanson , Harrison, William Henry , Hastie, William Henry , Hatch Act , Hate Crime , Have and Hold , Hawkers and Peddlers , Hayes, George E.C. , Hayes, Rutherford Birchard , Haymarket Riot , Haynsworth, Clement Furman, Jr. , Hays, William Harrison , Haywood, Margaret Austin , Haywood, William Dudley , Head of Household , Headnote , Health and Human Services Department , Health Care Law , Health Insurance , Hearing , Hearing Examiner , Hearsay , Hearst, Patty , Heart Balm Acts , Heat of Passion , Hedge Fund , Hegel, Georg Wilhelm Friedrich , Heightened Scrutiny , Heir , Held , Helms, Jesse Alexander, Jr. , Henceforth , Henry II of England , Henry, Patrick , Hereafter , Hereditament , Heritage Foundation , Hierarchy , Higginbotham, Aloyisus Leon, Jr. , High Crimes and Misdemeanors , Highway , Hijacking , Hill, Anita Faye , Hill, Oliver White, Sr. , Hirohito , Hiss, Alger , Hitler, Adolf , Hoar, Ebenezer Rockwood , Hobbes, Thomas , Hoffa, James Riddle , Hoffman, Walter Edward , Hold Harmless Agreement , Hold Over , Holder , Holder, Eric H., Jr. , Holder in due Course , Holding , Holding Company , Holiday , Holmes, Oliver Wendell, Jr. , Holograph , Home Rule , Homeland Security Department , Homeless Person , Homeowner's Warranty , Homestead , Homestead Act of 1862 , Homicide , Honor , Honorary Trust , Hooks, Benjamin Lawson , Hoover, Herbert Clark , Hoover, John Edgar , Hornblower, William Butler , Hornbook , Hostages , Hostile Fire , Hostile Witness , Hot Line Agreement, 1971 , Hot Pursuit , Hotchpot , House Arrest , House of Representatives , Housebreaking , Household , Housing and Urban Development Department , Houston, Charles Hamilton , Howard, Benjamin Chew , Hughes, Charles Evans , Human Rights , Human Rights Watch , Hume, David , Humphrey, Hubert Horatio , Hundred , Hung Jury , Hunt, Ward , Hunter, Elmo Bolton , Hunting , Huntley Hearing , Hurtado V. California , Husband and Wife , Hypothecate , Hypothesis , Hypothetical Question , Ibid , Idem , Identity Theft , I.E. , Illegitimacy , Illicit , Illusory Promise , Immaterial , Immediate Cause , Immigration , Imminent , Immunity , Immunization Programs , Impanel , Impartial , Impeach , Impeachment , Impediment , Impersonation , Impertinence , Impleader , Implied , Implied Consent , Implied Warranty , Import Quotas , Impossibility , Impostor Rule , Imposts , Impoundment , Impracticability , Imprimatur , Imprisonment , Improvements , Imputed , Imputed Knowledge , Imputed Notice , In Blank , In Camera , In Common , In Evidence , In Extremis , In Forma Pauperis , In Kind , In Lieu of , In Loco Parentis , In Medias Res , In Pari Delicto , In Pari Materia , In Perpetuity , In Personam , In Re , In Rem , In Specie , In Terrorem , Inadmissible , Inadvertence , Inalienable , Inc., , Incapacity , Incarceration , Incest , Inchoate , Incident of Ownership , Incidental , Incite , Income , Income Splitting , Income Tax , Incompatibility , Incompetency , Incompetent Evidence , Inconsistent , Incontestability Clause , Incorporate , Incorporation by Reference , Incorporation Doctrine , Incorporeal , Incremental , Incriminate , Inculpate , Incumbent , Incur , Indefeasible , Indefinite Term , Indemnify , Indemnity , Indenture , Independence , Independent Audit , Independent Contractor , Independent Counsel , Independent Parties , Indeterminate , Index , Index to Legal Periodicals , Indian Child Welfare Act , Indicia , Indictment , Indirect Evidence , Indispensable Party , Individual Retirement Account , Indorse , Indorsement , Inducement , Industrial Union , Industrial Workers of the World , Infamy , Infancy , Infants , Inference , Inferior Court , Infirmity , Information , Information and Belief , Informed Consent , Infra , Infraction , Infringement , Ingrossing , Inherent , Inherit , Inheritance , Initiative , Injunction , Injure , Injurious Falsehood , Injury , Inland Waters , Innkeeper , Innocent , Innocent Purchaser , Inns of Chancery , Inns of Court , Inoperative , Inquest , Inquiry, Commissions of , Inquisitorial System , Insanity Defense , Insecurity Clause , Insider , Insider Trading , Insolvency , Inspection , Installment , Instant , Instigate , Institute , Institution , Instructions , Instrument , Instrumentality Rule , Insurable Interest , Insurance , Insured , Insurer , Insurrection , Intangibles , Integrated , Integrated Agreement , Integrated Bar , Integration , Intellectual Property , Intemperance , Intent , Inter Alia , Inter Vivos , Interest , Interest on Lawyers Trust Account , Interference , Intergovernmental Immunity Doctrine , Interim , Interior Department , Interlineation , Interlocking Directorate , Interlocutory , Intermediate-Range Nuclear Forces Treaty , Internal Audit , Internal Revenue Code , Internal Revenue Service , International Court of Justice , International Criminal Court , International Law , International Monetary Fund , International Technology Law Association , International Trade Organization , International Waterways , Internet , Internet Fraud , Interpleader , Interpol , Interpolation , Interpretation , Interrogatories , Interstate Commerce Act , Interstate Commerce Commission , Interstate Compact , Intervening Cause , Intervenor , Intervention , Intestacy , Intestate , Intestate Succession , Intoxication , Intrinsic Evidence , Inure , Invalid , Inventory , Investiture , Investment , Invitation , Invitee , Invoice , Involuntary Confession , Involuntary Manslaughter , Involuntary Servitude , Ipse Dixit , Ipso Facto , Iran-Contra Affair , Iraq War , Iredell, James , Ireland, Patricia , Irreconcilable Differences , Irregularity , Irrelevant , Irreparable Injury , Irresistible Impulse , Irretrievable Breakdown of Marriage , Irrevocable , Island , Issue , Issue Preclusion , Itemize., v. 6. Jackson, Andrew , Jackson, Howell Edmunds , Jackson, Jesse Louis, Sr. , Jackson, Robert Houghwout , Jactitation , Jail , Jailhouse Lawyer , James, William , Japanese American Evacuation Cases , Jaworski, Leon , Jay, John , J.D. , Jefferson, Thomas , Jeopardy , Jetsam , Jim Crow Laws , Jobber , John Doe or Jane Doe , Johnson, Andrew , Johnson, Frank Minis, Jr. , Johnson, James Weldon , Johnson, Lyndon Baines , Johnson, Reverdy , Johnson, Thomas , Johnson, William , Joinder , Joint , Joint and Several Liability , Joint Estate , Joint Operating Agreement , Joint Resolution , Joint Stock Company , Joint Tenancy , Joint Tortfeasor , Joint Venture , Jones Act , Jones, Elaine Ruth , Jordan, Barbara Charline , Journal , J.P. , J.S.D. , Judge , Judge Advocate , Judgment , Judgment Creditor , Judgment Debtor , Judgment Docket , Judgment Note , Judgment Notwithstanding the Verdict , Judgment Proof , Judicare , Judicature , Judicature Acts , Judicial , Judicial Action , Judicial Administration , Judicial Assistance , Judicial Conference of the United States , Judicial Immunity , Judicial Notice , Judicial Review , Judicial Sale , Judicial Writs , Judiciary , Judiciary Act of 1789 , Junior , Junk Bond , Jural , Jurat , Juridical , Jurimetrics , Juris , Juris Doctor , Jurisdiction , Jurisdictional Dispute , Jurisprudence , Jurist , Juristic Act , Jury , Jury Commission , Jury Nullification , Jus , Jus Cogens , Jus Tertii , Just , Just Cause , Just Compensation , Just Desserts , Just War , Justice , Justice Department , Justice of the Peace , Justiciable , Justification , Justinian I , Juvenile Law , Kagan, Elena , Kangaroo Court , Kansas-Nebraska Act , Kant, Immanuel , Katzenbach, Nicholas Debelleville , Kearse, Amalya Lyle , Kefauver Investigation and Knapp Commission , Kellogg-Briand Pact , Kellogg, Frank Billings , Kelly, Sharon Pratt Dixon , Kelo V. City of New London , Kelsen, Hans , Kennedy, Anthony Mcleod , Kennedy, Edward Moore , Kennedy, John Fitzgerald , Kennedy, Robert Francis , Kent, James , Kent State Student Killings , Keogh Plan , Kevorkian, Jack , Key Numbers® , Keycite , Kickback , Kidnapping , Kilberg Doctrine , Kin , King, Edward , King, Martin Luther, Jr. , King, Rodney G. , King's Bench or Queen's Bench , Kissinger, Henry Alfred , Kiting , Kleindienst, Richard Gordon , Knaebel, Ernest , Know-Nothing Party , Knowingly , Knox, Philander Chase , Koop, Charles Everett , Korean War , Korematsu V. United States , Ku Klux Klan , Ku Klux Klan Act , Kunstler, William Moses , La Follette, Robert Marion , Labor-Management Relations Act , Labor Department , Labor Law , Labor Union , Laches , Lamar, Joseph Rucker , Lamar, Lucius Quintus Cincinnatus , Lame Duck , Lame-Duck Amendment , Land Grant , Land-Use Control , Landis, Kenesaw Mountain , Landlord , Landlord and Tenant , Landmark , Landrum-Griffin Act , Lanfranc , Langdell, Christopher Columbus , Lanham Act , Lapse , Larceny , Lasciviousness , Last Clear Chance , Last Resort , Latent , Lateral Support , Law , Law and Literature , Law Day , Law French , Law Journal , Law Merchant , Law of Nations , Law of the Case , Law of the Land , Law of the Sea , Law Reports , Law Review , Law School Admission Test , Lawful , Lawrence V. Texas , Lawsuit , Lawyer , Lawyer-Witness Rule , Lay , Layaway , Leading Case , Leading Question , League of Nations , League of United Latin American Citizens , Lease , Leaseback , Leasehold , Least Restrictive Means Test , Leave , Ledger , Lee, Charles , Lee V. Weisman , Legacy , Legal , Legal Advertising , Legal Age , Legal Aid , Legal Assistant , Legal Cap , Legal Cause , Legal Certainty , Legal Detriment , Legal Education , Legal Fiction , Legal History , Legal List Statutes , Legal Malpractice , Legal Positivism , Legal Proceedings , Legal Publishing , Legal Realism , Legal Representation , Legal Representative , Legal Reserve , Legal Residence , Legal Right , Legal Services Corporation , Legal Specialization , Legal Tender , Legal Title , Legalese , Legare, Hugh Swinton , Legatee , Legation , Leges Henrici , Legislate , Legislation , Legislative , Legislative Acts , Legislative Council , Legislative Court , Legislative Facts , Legislative History , Legislature , Legitimate , Lemon Laws , Lend-Lease Act , Lenin, Vladimir Ilyich , Leopold and Loeb Trial , Lessee , Lesser Included Offense , Lessor , Let , Letter of Credit , Letter of the Law , Letter Ruling , Letters of Administration , Letters Patent , Letters Rogatory , Letters Testamentary , Levees and Flood Control , Leverage , Levi, Edward Hirsch , Levy , Lewdness , Lewis, John Robert , Lex , Lex Fori , Lex Loci , Lexis® , Liability , Libel and Slander , Libelant , Libelous , Libertarian Party , Libertarianism , Liberty , Library of Congress , License , Licentiousness , Lien , Life Estate , Life in Being , Life or Limb , Lifo , Lift , Ligan , Limitation , Limitations of Actions , Limited , Limited Liability Company , Limited Liability Partnership , Limited Test Ban Treaty , Lincoln, Abraham , Lincoln, Levi , Lincoln, Robert Todd , Lindbergh Act , Lindbergh Kidnapping , Lindsey, Benjamin Barr , Line of Credit , Lineal , Lineup , Liquid Assets , Liquidate , Liquidated Damages , Liquidation , Liquormart V. Rhode Island , Lis Pendens , Listing , Litchfield Law School , Literal Construction , Literary Property , Litigation , Little-Collins, Ella Lee , Littleton, Sir Thomas , Littoral Rights , Litvinov Assignment of 1933 , Liuzzo, Viola Fauver Gregg , Livery of Seisin , Livery Stable Keepers , Living Trust , Living Will , Livingston, Edward , Livingston, Henry Brockholst , Livingston, Robert R. , LL. B. , Llewellyn, Karl Nickerson , LL. M. , Load Lines , Loan Commitment , Loan Shark , Lobbying , Local Action , Lochner V. New York , Locke, John , Lockout , Lockup , Lockwood, Belva Ann , Loco Parentis , Locus , Lodge, Henry Cabot , Lodger , Log Rolling , Logan Act , Logging , Logging in , Long-Arm Statute , Loophole , Loss , Loss of Services , Lost Instruments , Lot , Lott, Chester Trent , Louisiana Purchase , Low-Tide Elevation , Loyalty Oath , L.S. , Lump-Sum Settlement , Lurton, Horace Harmon , Lynching , MacKinnon, Catharine Alice , MacPherson V. Buick Motor Co. , MacVeagh, Isaac Wayne , Madison, James , Magistrate , Magna Carta , Magnuson-Moss Warranty Act , Mail Cover , Mail Fraud , Maine, Henry James Sumner , Maintenance , Maitland, Frederic William , Majority , Maker , Mala Fides , Mala in se , Mala Prohibita , Malcolm X , Malfeasance , Malice , Malice Aforethought , Malicious , Malicious Mischief , Malicious Prosecution , Malpractice , Man-in-the-House Rule , Managed Care , Manager , Mandamus , Mandate , Mandatory , Mandatory Authority , Mann Act , Mann, Horace , Mann, James Robert , Manor , Mansfield, William Murray, First Earl of , Manslaughter , Manufactures , Mapp V. Ohio , Marbury V. Madison , Margin , Margin Call , Maris, Albert Branson , Marital , Marital Communications Privilege , Maritime Lien , Market Value , Marketable Title , Marque and Reprisal , Marriage , Marshal , Marshaling Assets and Securities , Marshall, John , Marshall, Margaret Hilary , Marshall Plan , Marshall, Thurgood , Martial Law , Martin, Luther , Martin V. Hunter's Lessee , Martindale-Hubbell Law Directory , Marx, Karl Heinrich , Mason, George , Mason, John Young , Mass Communications Law , Massachusetts Constitution of 1780 , Massachusetts Trust , Massiah V. United States , Master , Master and Servant , Material , Mathews V., Eldridge Test , Matter of Fact , Matter of Law , Matter of Record , Matthews, Stanley , Maxim , Mayhem., v. 7. McCain, John Sidney , McCarran-Ferguson Act of 1945 , McCarran Internal Security Act , McCarran, Patrick Anthony , McCarthy, Eugene Joseph , McCarthy, Joseph Raymond , McClellan, John Little , McCulloch V. Maryland , McGrain V. Daugherty , McGranery, James Patrick , McGrath, James Howard , M.C.J. , McKenna, Joseph , McKinley, John , McKinley, William , McKinney Act , McLean, John , McNabb-Mallory Rule , McReynolds, James Clark , Mechanic's Lien , Mediation , Mediation, International Law , Medicaid , Medical Examiner , Medical Malpractice , Medicare , Meese, Edwin, III , Meeting of Creditors , Meeting of Minds , Megan's Law , Membership Corporation , Memorandum , Memorandum Decision , Mens Rea , Mensa et Thoro , Mental Anguish , Mental Cruelty , Mentschikoff, Soia , Mercantile , Merchantable , Mercian Law , Meredith, James Howard , Merger , Mergers and Acquisitions , Merit System , Merit Systems Protection Board , Merits , Mesne , Metes and Bounds , Mexico and the United States , Michelman, Kate , Michigan V. Tucker , Midnight Judges , Migratory Bird Treaty of 1918 , Military Government , Military Law , Military Occupation , Militia , Mill , Mill, John Stuart , Miller, Loren , Miller, Samuel Freeman , Miller V. California , Miller, William Henry Harrison , Millett, Katherine Murray , Milligan, ex Parte , Mine and Mineral Law , Mineral Right , Miner's Codes , Minimum Wage , Ministerial , Minitrial , Minor , Minority , Minton, Sherman , Minute Book , Minutes , Miranda V. Arizona , Miscarriage of Justice , Miscegenation , Mischief , Misdemeanor , Misfeasance , Misprision , Misrepresentation , Missouri Compromise of 1820 , Mistake , Mistake of Fact , Mistake of Law , Mistrial , Mitchell, John Newton , Mitchell, William de Witt , Mitigating Circumstances , Mitigation of Damages , Mittimus , Mixed Actions , M'Naghten Rule , Mock Trial , Model Acts , Model Penal Code , Modification , Modus Operandi , Moiety , Money Laundering , Money Paid , Monopoly , Monroe Doctrine , Monroe, James , Montesquieu, Charles-Louis de Secondat, Baron de la Brède et de , Montgomery Bus Boycott , Monument , Moody, William Henry , Moore, Alfred , Moot , Moot Court , Moral Law , Moral Relativism , Moral Turpitude , Moratorium , Mormon Church , Mortality Tables , Mortgage , Mortmain , Mortmain Acts , Moseley Braun, Carol Elizabeth , Most-Favored-Nation Status , Mothers Against Drunk Driving , Motion , Motive , Motley, Constance Baker , Movant , Move , Movie Rating , Mueller, Robert Swann, III , Mukasey, Michael B. , Multidistrict Litigation , Multilevel Distributorship , Multiplicity of Actions , Municipal , Municipal Corporation , Muniments of Title , Murder , Murphy, Francis William , Music Publishing , Mussey, Ellen Spencer , Mussolini, Benito , Mutilation , Mutiny , Mutual Company , Mutual Fund , Mutual Mistake , Mutuality of Obligation , My Lai Massacre , Naacp , Naacp Legal Defense and Educational Fund , Nader, Ralph , Naked Contract , Name , Napoleonic Code , Naral Pro-Choice America , Narcotics Acts , Nation of Islam , National Association of Broadcasters , National Association of Manufacturers , National Association of Realtors , National Character of Aircraft , National Cooperative Bank , National Council of la Raza , National Credit Union Administration , National Education Association , National Environmental Policy ACT of 1969 , National Federation of Independent Businesses , National Firearms Act of 1934 , National Gay and Lesbian Task Force , National Guard , National Health Care , National Industrial Recovery Act of 1933 , National Intelligence Program , National Labor Relations Board , National Mediation Board , National Organization for the Reform of Marijuana Laws , National Organization for Women , National Recovery Administration , National Rifle Association , National Right to Life Committee , National Security Council , National Transportation Safety Board , National Urban League , Native American Graves Protection and Repatriation Act of 1990 , Native American Rights , Natural and Probable Consequences , Natural Law , Natural Law Party , Naturalization , Navigable Waters , Navy Department , Near V. Minnesota , Necessaries , Necessary and Proper Clause , Necessity , Negative Covenant , Neglect , Negligence , Negligent Entrustment , Negotiable Instrument , Negotiate , Nelson, John , Nelson, Samuel , Net , Net Worth , Neutrality , New Deal , New Party , New York Constitution of 1777 , New York Times Co. V. Sullivan , New York Times Co. V. United States , Newton, Huey Percy , Next Friend , Next of Kin , Nihil , Nimmer, Melville Bernard , Nineteenth Amendment , Ninety-Day Letter , Ninth Amendment , Nisi Prius , Nixon, Richard Milhous , Nixon, United States V. , Nlrb V. Jones & Laughlin Steel Corp. , No Bill , No Contest , No Fault , No-Load Fund , Nolle Prosequi , Nolo Contendere , Nominal , Nominal Damages , Non , Non Prosequitur , Non Sui Juris , Non Vult Contendere , Nonage , Noncompete Agreement , Nonconforming Use , Nonfeasance , Nonprofit , Nonsuit , Nonsupport , Norris, George William , Norris-LaGuardia Act , North American Free Trade Agreement , North Atlantic Treaty Organization , North Pacific Fisheries Convention, 1952 , Northwest Atlantic Fisheries Convention, 1949 , Northwest Ordinance , Norton, Eleanor Holmes , Notary Public , Note , Notes of Decisions , Notice , Novation , Nuclear Nonproliferation Treaty , Nuclear Power , Nuclear Regulatory Commission , Nuclear Weapons , Nugatory , Nuisance , Null , Nunc Pro Tunc , Nuncupative Will , Nuremberg Trials , Oath , Obama, Barack Hussein, Jr. , Obiter Dictum , Object , Objection , Objective Theory of Contract , Obligation , Obligee , Obligor , Obliteration , Obscene , Obscenity , Obstruction of Justice , Occupancy , Occupational Disease , Occupational Safety and Health Act of 1970 , O'Connor, Sandra Day , O'Conor, Charles , Of Counsel , Of Course , Of Record , Offense , Offer , Office Audit , Office of Management and Budget , Office of National Drug Control Policy , Office of Thrift Supervision , Officer , Officers of the Court , Official Gazette , Offset , Old-Age, Survivors, and Disability Insurance , Olmstead V. United States , Olney, Richard , Ombudsperson , Omnibus , On Demand , On or About , On Point , One Person, One Vote , O'Neill, Thomas Phillip, Jr. , Onus Probandi , Open , Open Account , Open Bid , Open Court , Open-End Contract , Open-End Credit , Open-End Mortgage , Open Listing , Open Shop , Opening Statement , Operation of Law , Opinion Evidence , Oppression , Option , Oral Contract , Ordeal , Order , Order of the Coif , Ordinance , Organ Donation Law , Organ Transplantation , Organic Law , Organization , Organized Crime , Original Intent , Original Jurisdiction , Original Writ , Origination Fee , Orphan's Court , Ostensible , Otis, James, Jr. , Otto, William Tod , Out-of-Court Settlement , Outlawry , Output Contract , Outstanding Warrant , Overbreadth Doctrine , Overdraft , Overhead , Overreaching , Override , Overrule , Overt , Overt Act , Owner , Oyer and Terminer , Oyez , Pacific Railroad Act , Pacifism , Packing , Pact , Pacta Sunt Servanda , Pactum , Page, Alan Cedric , Paine, Robert Treat , Paine, Thomas , Pairing-Off , Pais , Palm Off , Palmer, Alexander Mitchell , Palpable , Palsgraf V., Long Island Railroad Company , Pander , Panel , Paper , Par , Parallel Citation , Paramount Title , Parcener , Pardon , Parens Patriae , Parent and Child , Parent Company , Pari Causa , Pari Delicto , Pari Materia , Pari Passu , Parity , Parks, Rosa Louise McCauley , Parliamentary Law , Parody , Parol Evidence , Parole , Parsons, Theophilus , Particular Average Loss , Particulars , Parties , Partition , Partnership , Party , Party of the First Part , Party Wall , Pass , Passim , Passport , Pat. Pend. , Patent , Patent and Trademark Office , Patent Troll , Patent Writ , Patents , Paternity , Paternity Suit , Paterson, William , Patients' Rights , Patronage , Paul, Alice Stokes , Pauper , Pawn , Pawnbroker , Payable , Payee , Payment , P.C. , Peace Bond , Peace Officers , Peckham, Rufus Wheeler , Peculation , Pecuniary , Pederasty , Peers , Pen Register , Penal , Penalty , Pendent Jurisdiction , Pendente Lite , Pending , Pendleton, George Hunt , Penitentiary , Pennsylvania Constitution of 1776 , Penny Stocks , Penology , Pension , Pent Road , Penumbra , Peonage , People , People for the Ethical Treatment of Animals , Per , Per Capita , Per Curiam , Per Quod , Per Se , Per Stirpes , Percentage Lease , Peremptory Challenge , Peremptory Ruling , Perfect , Performance , Peril , Perjury , Perkins, Frances , Permissive Counterclaim , Perpetrator , Perpetuating Testimony , Perpetuation of Evidence , Perquisites , Person , Personal Actions , Personal Injury , Personal Jurisdiction , Personal Property , Personal Representative , Personal Service , Personalty , Persuasive Authority , Petit Jury , Petit Larceny , Petition , Petition in Bankruptcy , Petitioner , Petitory Action , Petty Offense , Philadelphia Lawyer , Photo Lineup , Physical Fact , Physicians and Surgeons , Picketing , Pierce, Franklin , Pierrepont, Edwards , Pilot , Pimp , Pinkerton Agents , Pinkerton, Allan , Pinkney, William , Piracy , Pitney, Mahlon , P.J. , Plagiarism , Plain-Error Rule , Plain-Meaning Rule , Plain View Doctrine , Plaintiff , Plaintiff in Error , Plat , Plea , Plea Bargaining , Plea in Abatement , Plea in Bar , Pleading , Pledge , Plessy V. Ferguson , Plur..., v. 8. Poaching , Pocket Part , Point , Poison , Poison Pill , Police , Police and Guards, Private , Police Corruption and Misconduct , Police Power , Policy , Political Action Committee , Political Campaign Law , Political Crime , Political Question , Political Trial , Polk, James Knox , Poll Tax , Pollack, Milton , Pollak, Walter Heilprin , Polling the Jury , Pollock, Frederick , Pollock V. Farmers' Loan & Trust Co. , Polls , Pollution , Polygamy , Polygraph , Ponzi Scheme , Popular Name Tables , Pornography , Positive Evidence , Positive Law , Positivism , Posner, Richard Allen , Posse Comitatus , Possession , Possessory Action , Possessory Warrant , Post Mortem , Postconviction Remedies , Postdate , Posthumous Child , Posting , Postmarital Agreement , Pound, Roscoe , Pour-Over , Powell, Adam Clayton, Jr. , Powell, Lewis Franklin, Jr. , Powell V. Alabama , Power , Power of Attorney , Power of Sale , Power of Termination , Practice , Practice of Law , Praecipe , Prayer , Preamble , Precatory Language , Precedent , Precept , Precinct , Preclusion Order , Preemption , Preemptive Right , Preference , Preferred Stock , Prejudice , Prelaw Education , Preliminary Hearing , Preliminary Injunction , Premarital Agreement , Premeditate , Premium , Preponderance of Evidence , Prerogative , Prerogative Writ , Prescription , Present , Presentence Investigation , Presentment , Presents , President of the United States , Presidential Powers , Presumption , Presumption of Innocence , Pretermitted Heir , Pretrial Conference , Pretrial Publicity , Prevailing Party , Preventive Detention , Price-Fixing , Prigg V. Pennsylvania , Prima Facie , Primary Authority , Primary Evidence , Prime Lending Rate , Primogeniture , Principal , Principal and Surety , Principle , Printers Ink Statute , Prior Inconsistent Statements , Prior Restraint , Prison , Prisoners' Rights , Privacy , Privacy Act of 1974 , Private , Private Attorney General , Private Bill , Private International Law , Private Law , Private Roads , Privateer , Privilege , Privilege Against Self-Incrimination , Privileged Communication , Privileges and Immunities , Privity , Privy , Privy Council , Prize , Prize Courts , Prize Law , Pro , Pro Bono , Pro Forma , Pro Hac Vice , Pro Rata , Pro Se , Pro Tanto , Pro Tem , Probable Cause , Probate , Probation , Probationer , Probative , Procedural Law , Procedure , Proceeding , Proceeds , Process , Process Server , Proclamation , Proctor , Procure , Produce , Product Liability , Profanity , Professio Juris , Professional Responsibility , Proffer , Profit , Profit a Prendre , Progressive Party , Progressive Tax , Prohibition , Prohibition Party , Prohibition, Writ of , Promise , Promissory Estoppel , Promissory Note , Promoter , Promulgate , Proof , Proper , Property Law , Property Right , Property Settlement , Proponent , Propound , Proprietary , Prorate , Prorogation , Prosecute , Prosecutor , Prospectus , Prostitution , Protective Custody , Protective Order , Protectorate , Protest , Prothonotary , Protocol , Province , Provisional , Proviso , Provocation , Proximate Cause , Proxy , Prudent Person Rule , Public , Public Administrative Bodies , Public Contract , Public Defender , Public Domain , Public Figure , Public Health Service , Public Interest , Public Lands , Public Law , Public Offering , Public Policy , Public Utilities , Publication , Publish , Publishing Law , Puerto Rico and the United States , Puffing , Pullman Strike , Punishment , Punitive Damages , Purchase , Purchase Money Mortgage , Purchase Order , Pure Food and Drug Act of 1906 , Pure Speech , Purge , Purport , Pursuant , Purview , Put , Putative , Putzel, Henry, Jr. , Qua , Qualification , Qualified Acceptance , Quantum Meruit , Quantum Valebant , Quare , Quash , Quasi , Quasi Contract , Quasi in Rem Jurisdiction , Quasi-Judicial , Quasi-Legislative , Question of Fact , Question of Law , Qui Tam Actions , Quick Assets , Quid Pro Quo , Quiet Enjoyment , Quiet Title Action , Quinlan, In Re , Quit , Quitclaim Deed , Quo Animo , Quo Warranto , Quorum , Racial and Ethnic Discrimination , Racial Profiling , Racketeering , Railroad , Railroad Retirement Act , Ramo, Roberta Cooper , Randolph, Asa Philip , Randolph, Edmund Jennings , Rankin, Jeannette , Rantoul, Robert, Jr. , Rape , Ratable , Rate , Ratification , Ratio Decidendi , Rational Basis Test , Ravishment , Rawls, John Bordley , Re , Reagan, Ronald Wilson , Real , Real Actions , Real Estate , Real Evidence , Realized , Reasonable , Reasonable Doubt , Reasonable Force , Reasonable Person , Reasonable Time , Reasonable Woman , Rebate , Rebus Sic Stantibus , Rebut , Rebuttable Presumption , Rebutter , Recall , Recaption , Receipt , Receiver , Receivership , Receiving Stolen Property , Recess , Recidivism , Reciprocal , Recital , Recklessness , Recognition , Recognizance , Reconciliation , Reconstruction , Reconveyance , Recording of Land Titles , Records , Recoupment , Recourse , Recovered Memory , Recovery , Recrimination , Recuse , Red Scare , Redemption , Redlining , Redress , Reductio Ad Absurdum , Reed, Stanley Forman , Referee , Reference , Referendum , Reform Party , Reformation , Reformatories , Refreshing Memory , Refugees , Refunding , Regents of the University of California V. Bakke , Register , Register of Deeds , Registrar , Registration , Registration of Land Titles , Regressive Tax , Regular , Regulation , Rehabilitation , Rehnquist, William Hubbs , Reinstate , Reinsurance , Rejoinder , Relation , Relator , Release , Release Time Program , Relevancy , Relief , Religion , Remainder , Remand , Remedial Statute , Remedy , Remission , Remit , Remittance , Remittitur , Removal , Render , Renewal , Reno, Janet , Rent Strike , Renunciation , Renunciation of War , Renvoi , Reorganization , Reorganization Plan , Reparable Injury , Reparation , Repeal , Replevin , Replication , Reply , Report , Reporter , Repossession , Represent , Representation , Representative , Representative Action , Reprieve , Reprisal , Reproduction , Republic , Republican Party , Republication , Repudiation , Repugnancy , Requirements Contract , Requisition , Res , Res Gestae , Res Ipsa Loquitur , Res Judicata , Rescind , Rescission , Rescue , Rescue Doctrine , Reservation , Reserve , Residence , Residency , Residuary Clause , Residuum , Resolution , Respondeat Superior , Respondent , Responsive Pleading , Rest , Restatement of Law , Restitution , Restorative Justice , Restraining Order , Restraint of Trade , Restrictive Covenant , Restrictive Indorsement , Resulting Trust , Retainer , Retaliatory Eviction , Retorsion , Retraction , Retro , Retroactive , Return , Return Day , Revenue , Reverse , Reversion , Reverter, Possibility of , Review , Revised Statutes , Revival of an Action , Revive , Revocation , Revoke , Revolution , Revolving Charge , Reward , Rex , Reynolds v. Sims , Richardson, Elliot Lee , Rider , Ridge, Thomas Joseph , Right , Right of Action , Right of Election , Right of Reentry , Right of Survivorship , Right of Way , Right to Counsel , Right-to-Work Laws , Riot , Riparian Rights , Ripeness , Risk , Risk Arbitrage , Robbery , Roberts, John Glover, Jr. , Roberts, Owen Josephus , Roberts v. United States Jaycees , Robinson-Patman Act , Robinson, Spottswood William, III , Robinson V. California , Rochin V. California , Rodney, Caesar Augustus , Roe , Roe v. Wade , Rogers, William Pierce , Roll , Roman Law , Romer v., Evans , Roosevelt, Anna Eleanor , Roosevelt, Franklin Delano , Roosevelt, Theodore , Rosenbergs Trial , Ross, John , Ross, Nellie Tayloe , Rostker v. Goldberg , Roth v. United States , Rousseau, Jean Jacques , Royalty , Rubric of a Statute , Ruby, Jack , Rule , Rule Against Accumulations , Rule Against Perpetuities , Rule in Shelley's Case , Rule of 78 , Rule of Law , Rules of Decision Act , Rules of War , Ruling , Run , Running with the Land , Rush, Benjamin , Rush, Richard , Rutledge, John , Rutledge, Wiley Blount, Jr. , Rylands v. Fletcher , S Corporation , Sabotage , Sacco and Vanzetti Trial , Said , Sailor , Salem Witch Trials , Sales Law , Sales Tax , Salvage , Same Conduct Test , Same Evidence Test , San Francisco Vigilance Committees of 1851 and 1856 , Sanction , Sanford, Edward Terry , Sanger, Margaret Higgins , Sanity , Santa Clara County V. Southern Pacific Railroad Company., v. 9. Sarbanes-Oxley Act of 2002 , Sargent, John Garibaldi , Satisfaction , Save , Saving Clause , Savings and Loan Association , Saxbe, William Bart , Scab , Scalia, Antonin , Schechter Poultry Corp. V. United States , Schenck V. United States , Schlafly, Phyllis Stewart , Schlesinger, Rudolf Berthold , School Desegregation , Schools and School Districts , Scienter , Scientific Evidence , Scintilla , Scire Facias , Scope of Employment , Scopes Monkey Trial , Scorched-Earth Plan , Seabed Arms Control Treaty of 1971 , Seal , Seal of the United States , Sealed Verdict , Search and Seizure , Search Warrant , Seasonable , Seat Belts , Sec , Secession , Second Amendment , Second Look Doctrine , Secondary Authority , Secondary Boycott , Secondary Evidence , Secondary Meaning , Secret Service , Secretary of State , Section , Section 1983 , Secure , Secured Creditor , Secured Transactions , Securities , Securities and Exchange Commission , Security , Security Deposit , Sedition , Seditious Libel , Seduction , Segregation , Seizure , Selden, John , Selden Society , Selective Prosecution , Selective Service System , Selectman or Selectwoman , Self-Dealing , Self-Defense , Self-Determination , Self-Executing , Self-Executing Treaty , Self-Help , Self-Incrimination , Senate , Senate Judiciary Committee , Seneca Falls Convention , Senior Citizens , Senior Interest , Seniority , Sentencing , Separate but Equal , Separate Maintenance , Separation , Separation of Powers , September 11th Attacks , Sequestration , Seriatim , Serjeant at Law , Service , Service Mark , Service of Process , Servicemembers Civil Relief Act , Servitude , Session , Set Aside , Set Down , Set-Off , Setback , Settle , Settlement , Settlement Statement , Settlor , Seven Bishops' Trial , Seventeenth Amendment , Seventh Amendment , Severable , Several , Severalty Ownership , Severance , Sex Discrimination , Sex Offenses , Sexual Abuse , Sexual Harassment , Sham , Shapiro, Robert Leslie , Share , Shaw, Lemuel , Shaw V. Hunt , Shays's Rebellion , Shelter , Shepardizing , Shepard's® Citations , Sheppard, Samuel H. , Sheriff , Sheriff's Deed , Sherman Anti-Trust Act , Sherman Compromise , Sherman, John , Sherman, Roger , Shield Laws , Shifting the Burden of Proof , Shipping Law , Shiras, George, Jr. , Shock-The-Conscience Test , Shop-Book Rule , Shop Steward , Shoplifting , Short Cause , Short Sale , Show Cause , Show Cause Order , Show-Up , Sic , Sierra Club , Sight Draft , Signature , Simple , Simpson, O.J. , Simultaneous Death , Sinclair, Upton Beall , Sine Die , Sine Qua Non , Single Name Paper , Single Name Partnership , Sit , Situs , Sixteenth Amendment , Sixth Amendment , S.J.D. , Slating , Slaughter-House Cases , Slavery , Slip Decision , Slip Law , Small Business , Small Business Administration , Small Claims Court , Smart Money , Smith Act , Smith, Mary Louise , Smith, Robert , Smith, William French , Smuggling , Social Security , Social Security Act of 1935 , Socialism , Socialist Party of the United States of America , Sodomy , Software , Sole Proprietorship , Solicitation , Solicitor , Solicitor General , Solid Wastes, Hazardous Substances, and Toxic Pollutants , Solomon Amendment , Solvency , Son of Sam Laws , Sonosky, Marvin J. , Sony Corp. of America V. Universal City Studios , Sotomayor, Sonia Maria , Souter, David Hackett , Southeast Asia Treaty Organization , Southern Christian Leadership Conference , Southern Poverty Law Center , Sovereign Immunity , Sovereignty , Spanish-American War , Special Appearance , Special Assessment , Special Courts , Special Damages , Special Master , Special Term , Special Verdict , Special Warranty Deed , Specialization , Specialty , Specific Intent , Specific Legacy , Specific Performance , Speculative Damages , Speech or Debate Clause , Speed, James , Speedy Trial , Spending Power , Spendthrift , Spendthrift Trust , Spin-Off , Split Decision , Split-Off , Split-Up , Spoliation , Sporkin, Stanley , Sports Law , Spot Zoning , Squatter , SS , St. Clair, James Draper , Stale Check , Stalin, Joseph , Stalking , Stamp Act , Stamp Tax , Stanbery, Henry , Stand , Stand Mute , Standard Deduction , Standing , Stanford, Amasa Leland , Stanton, Edwin Mcmasters , Stanton, Elizabeth Cady , Star Chamber , Stare Decisis , Starr, Kenneth Winston , Start Treaties , Start I , Start II , Start III and Sort , State , State Action , State Courts , State Department , State Department of Motor Vehicles , State Interest , State Lottery , Statement of Affairs , State's Evidence , States' Rights , States' Rights Party , Status , Status Offense , Status Quo , Statute , Statute of Frauds , Statute of Limitations , Statute of Uses , Statute of Wills , Statute of York , Statutes at Large , Statutory , Statutory Rape , Statutory Redemption , Stay , Steering , Steinem, Gloria , Stenographer , Sterilization , Stevens, John Paul , Stevenson, Adlai Ewing , Stewart, Potter , Stimson, Henry Lewis , Stipulation , Stock , Stock Dividend , Stock Market , Stock Option , Stock Warrant , Stockholder's Derivative Suit , Stone, Harlan Fiske , Stone, Lucy , Stop and Frisk , Stop Order , Stop Payment Order , Stoppage in Transit , Story, Joseph , Stout, Juanita Kidd , Stowe, Harriet Beecher , Straddle , Straight-Line Depreciation , Stranger , Strategic Lawsuits Against Public Participation , Straw Man , Street Railroad , Strict Construction , Strict Foreclosure , Strict Liability , Strict Scrutiny , Strike , String Citation , Strong-Arm Provision , Strong, William , Strossen, Nadine M. , Struck Jury , Student Nonviolent Coordinating Committee , Sua Sponte , Sub Nomine , Sub Silentio , Subcontractor , Subject Matter Jurisdiction , Subletting , Submerged Lands , Submission of Controversy , Submit , Subordination , Subornation of Perjury , Subpoena , Subpoena Duces Tecum , Subrogation , Subscribe , Subscription , Subsidiary , Substance , Substance Abuse and Mental Health Services Administration , Substantial , Substantiate , Substantive Due Process , Substantive Law , Substituted Service , Succession , Succession of States , Sue , Suffer , Suffrage , Sui Generis , Sui Juris , Suicide , Summary , Summary Judgment , Summary Proceedings , Summary Process , Summons , Sumner, Charles , Sumptuary Laws , Sunset Provision , Sunshine Laws , Superior , Supersede , Supersedeas , Supervening , Supplementary Proceedings , Support , Suppress , Supra , Supremacy Clause , Supreme Court , Supreme Court Historical Society , Supreme Court of the United States , Surcharge , Surety , Surgeon General , Surplusage , Surprise , Surrebutter , Surrejoinder , Surrender , Surrogate Court , Surrogate Motherhood , Surtax , Suspect Classification , Suspended Sentence , Suspicion , Sustain , Sutherland, George , Swann V. Charlotte-Mecklenburg Board of Education , Swat Teams , Swayne, Noah Haynes , Swift V., Tyson , Syllabus , Symbolic Delivery , Symbolic Speech , Syndicate , Synopsis , Table of Cases , Tacit , Tacking , Taft-Hartley Act , Taft, Alphonso , Taft, William Howard , Tail , Takeover , Talesman , Tamm, Edward Allen , Tammany Hall , Tamper , Taney, Roger Brooke , Tangible , Tariff , Tax Avoidance , Tax Court , Tax Deed , Tax Evasion , Tax Rate , Tax Reform Act of 1986 , Tax Return , Tax Sale , Taxable Income , Taxable Situs , Taxation , Taxing Costs , Taxpayer Bill of Rights , Taxpayer's Suit , Taylor, Zachary , Teapot Dome Scandal , Telecommunications , Television , Temperance Movement , Temporary Emergency Court of Appeals , Temporary Restraining Order , Tenancy , Tenancy by the Entirety , Tenancy in Common , Tenancy in Coparcenary , Tenant , Tender , Tender Offer , Tender Years Doctrine , Tenement , Tennessee Valley Authority , Tennessee Valley Authority Act , Tenor , Tenth Amendment , Tenure , Tenure of Office Act., v. 10. Term , Term of Art , Termination , Terrell, Mary Eliza Church , Territorial Courts , Territorial Waters , Territoriality , Territories of the United States , Territory , Terrorism , Terry v. Ohio , Test Case , Testacy , Testament , Testamentary , Testate , Testator , Testify , Testimony , Texas v. Johnson , Texas v. White , Theaters and Shows , Theft , Theodosian Code , Third Amendment , Third Degree , Third Party , Thirteenth Amendment , Thomas, Clarence , Thompson, Smith , Thoreau, Henry David , Thornburgh, Richard Lewis , Threats , Three Strikes Laws , Thurmond, James Strom , Tilden, Samuel Jones , Time , Time Draft , Time is of the Essence , Time, Place, and Manner Restrictions , Time-Price Differential , Timely , Timeshare , Tinker v. Des Moines Independent Community School District , Tithing , Title , Title Insurance , Title Search , To Wit , Tobacco , Tobacco Institute , Todd, Thomas , Tokyo Trial , Toll , Tonkin Gulf Resolution , Tontine , Torrens Title System , Tort Law , Tortfeasor , Tortious , Totten Trust , Toucey, Isaac , Towage Service , Town , Townshend Acts , Township , Tracing , Trade Dress , Trade Name , Trade Secret , Trade Union , Trade Usage , Trademarks , Trading Stamps and Coupons , Transcript , Transfer , Transfer of Assets , Transfer Tax , Transitory Action , Transnational Corporation , Transnational Law , Transportation Department , Trask, Mililani B. , Traverse , Traynor, Roger John , Treason , Treasury Department , Treasury Stock , Treaties in Force , Treatise , Treaty , Treaty of Paris , Treaty of Versailles , Treble Damages , Trent Affair , Trespass , Trespass to Try Title , Trial , Triangle Shirtwaist Company Fire , Tribunal , Trimble, Robert , Trover , True Bill , Truman, Harry S , Trust , Trust Company , Trust Deed , Trust Receipt , Trustee , Trustees of Dartmouth College v. Woodward , Trusties , Truth in Lending Act , Truth, Sojourner , Try , Tucker Act , Tuskegee Syphilis Study , Tuttle, Elbert Parr , Twelfth Amendment , Twentieth Amendment , Twenty-Fifth Amendment , Twenty-First Amendment , Twenty-Fourth Amendment , Twenty-Second Amendment , Twenty-Seventh Amendment , Twenty-Sixth Amendment , Twenty-Third Amendment , Tying Arrangement , Tyler, John , Ultimate Facts , Ultra Vires , Umpire , Unauthorized Practice , Unconscionable , Underinclusiveness , Understanding , Undertaking , Underwrite , Undue Influence , Unemployment Compensation , Unenumerated Rights , Unethical Conduct , Unfair Competition , Unfair Labor Practice , Uniform Acts , Uniform Code of Military Justice , Uniform Commercial Code , Uniform Computer Information Transactions Act , Uniform Consumer Credit Code , Uniform Crime Reports , Uniform Probate Code , Unilateral Contract , Union Shop , United Farm Workers of America , United Nations , United States Government Manual , United Steelworkers v. Weber , Unities , Unitrust , Unjust Enrichment , Unlawful , Unlawful Assembly , Unlawful Communications , Unlawful Detainer , Unliquidated , Unwritten Law , Upset Price , U.S. Chamber of Commerce , U.S. Civil War , U.S. Code , U.S. Code Annotated® , U.S. Commissioners , U.S. Court of Appeals for Veterans Claims , U.S. Courts of Appeals , U.S. Information Agency , U.S. Marshals Service , U.S. Postal Service , U.S. Sentencing Commission , U.S. Trade Representative, Office of , USA Patriot Act of 2001 , Usage , USCCAN® , USDC , Use , Use and Occupation , Use Tax , Usufruct , Usurpation , Usury , Uti Possidetis , Utilitarianism , Utter , Uxor , Vacate , Vagrancy , Vague , Valid , Valuable Consideration , Valuation , Value , Van Buren, Martin , Van Devanter, Willis , Vandalism , Vanderbilt, Arthur T. , Variance , Vaughn, George L. , Vel Non , Vendee , Vendor , Vendor and Purchaser , Venire Facias , Venireman , Venue , Verba , Verdict , Verify , Versus , Vertical Merger , Vest , Veterans Affairs Department , Veterans of Foreign Wars , Veterans' Rights , Veto , Vexatious Litigation , Vicarious Liability , Vice , Vice Crimes , Vice President , Victim-Assistance Program , Victimless Crimes , Victims of Crime , Victims of Crime Act of 1984 , Vidal v. Girard's Executors , Vietnam War , Vigilantism , Vill , Vinson, Frederick Moore , Violence Against Women Act of 1994 , Violent Crime Control and Law Enforcement Act of 1994 , Virginia and Kentucky Resolves , Virginia Conventions , Virginia Declaration of Rights , Virginia, United States v. , Vis , Visa , Visible Means of Support , Visitation Rights , Vitiate , Vitoria, Francisco de , Viva Voce , Viz. , Void , Void for Vagueness Doctrine , Voidable , Voir Dire , Volenti Non Fit Injuria , Volstead Act , Volstead, Andrew John , Voluntary Act , Voting , Voting Rights Act of 1965 , Voting Trust , Vouchee , Voucher , Vouching-in , Wadset , Wage Assignment , Wage Earner's Plan , Wager of Battel , Wager of Law , Wagner Act , Wagner, Robert Ferdinand , Wait-and-See Doctrine , Waite, Morrison Remick , Waive , Waiver , Waiving Time , Wald, Patricia McGowan , Wallace, George Corley , Wallace, John William , Wallace v. Jaffree , Walnut Street Prison , Want , Want of Consideration , Wanton , Wapentake , War , War Crimes , War of 1812 , War of Independence , War on Terrorism , Ward , Ward, Nathaniel , Warehouse Receipt , Warehouseman , Warrant , Warrant of Attorney , Warranty , Warranty Deed , Warren, Charles , Warren Commission , Warren Court , Warren, Earl , Wash Sale , Washington, Booker Taliaferro , Washington, Bushrod , Washington, George , Washington v. Glucksberg , Waste , Water Pollution , Water Rights , Watergate , Wattleton, Alyce Faye , Wayne, James Moore , Weapons , Weapons of Mass Destruction , Weber, Max , Webster, Daniel , Webster v. Reproductive Health Services , Weddington, Sarah Ragle , Weight of Evidence , Weights and Measures , Weinstein, Jack Bertrand , Weis, Joseph Francis, Jr. , Welch, Joseph Nye , Welfare , Wells-Barnett, Ida Bell , Welsh v. United States , Wesley, Carter Walker , West Coast Hotel Co. V. Parrish , West Legal Directory , West Saxon Lage , Westlaw® , Westminster, First Statute of , Westminster Hall , Westminster, Second Statute of , Whaling , Wharves , Wheaton, Henry , Wheaton v. Peters , Whereas , Whereby , Wherefore , Whig Party , Whiskey Rebellion , Whistleblowing , White, Byron Raymond , White-Collar Crime , White, Edward Douglass , White Primary , White Supremacy Groups , Whiteacre , Whiteman, Marjorie Millace , Whitewater , Whittaker, Charles Evans , Wickersham Commission , Wickersham, George Woodward , Wigmore, John Henry , Wildcat Strike , Wilde, Oscar , Wilkins, Roy Ottoway , Will , Will, Hubert Louis , Willful , Williams Act , Williams, Franklin Hall , Williams, George Henry , Williston, Samuel , Wilmot, David , Wilmot Proviso , Wilson, James , Wilson, James Quinn , Wilson, Thomas Woodrow , Wind Up , Winship, in re , Wiretapping , Wirt, William , Wisdom, John Minor , Witan , Witherspoon v. Illinois , Withholding Tax , Within the Statute , Without Day , Without Prejudice , Without Recourse , Witness Stand , Witnesses , Wolcott, Alexander , Women's Rights , Woodbury, Levi , Woods and Forests , Woods, William Burnham , Words and Phrases® , Words of Art , Words of Limitation , Words of Purchase , Work Product Rule , Workers' Compensation , World Bank , World War I , World War II , Worthier Title Doctrine , Wright, James Skelly , Writ , Writs of Assistance Case , Wrong , Wrongful Birth , Wrongful Death , Wrongful Discharge , Wrongful Life , Wrongful Pregnancy , Wyatt, Walter , Wygant v., Jackson Board of Education , Wythe, George , "X" as a Signature , X Rating , XYY Chromosomal Abnormality Defense , XYZ Affair , Yalta Agreement , Year Books , Yellow Dog Contract , Yick Wo v. Hopkins , Yield , York-Antwerp Rules , Young, Owen D. , Youngstown Sheet & Tube Co. v. Sawyer , Zenger, John Peter, Trial , Zero Bracket Amount , Zero Tolerance , Zoning., v. 11. Milestones in the Law , Brown v. Board of Education of Topeka, Kansas , District of Columbia v. Heller , Gideon v. Wainwright , Kelo v. City of New London., v. 12. Milestones in the Law , Lawrence V. Texas , Mapp V. Ohio , Marbury V. Madison , Miranda V. Arizona , New York Times V. Sullivan , Roe V. Wade., v. 13. Primary Documents , Foundations of U.S. Law , English Law , English Law: Magna Charta , English Law: English Bill of Rights , English Law: Second Treatise on Government , The Colonial Period , The Colonial Period: Mayflower Compact , The Colonial Period: The Laws and Liberties of Massachusetts , The Colonial Period: Frame of Government , The Colonial Period: South Carolina Slave Code , Conflict and Revolution , Conflict and Revolution: Stamp Act , Conflict and Revolution: Townshend Acts , Conflict and Revolution: Declaration of the Causes and Necessity of Taking up Arms , Conflict and Revolution: Common Sense , Conflict and Revolution: Virginia Declaration of Rights , Conflict and Revolution: Declaration of Independence , Conflict and Revolution: Treaty of Paris , Origins of U.S. Government , Origins of U.S. Government: Articles of Confederation , Origins of U.S. Government: Northwest Ordinance , Origins of U.S. Government: The Virginia, or Randolph, Plan , Origins of U.S. Government: The New Jersey, or Paterson, Plan , Origins of U.S. Government: Constitution of the United States , Origins of U.S. Government: Bill of Rights , Origins of U.S. Government: Federalist, Number 10 , Origins of U.S. Government: Federalist, Number 78 , Origins of U.S. Government: The Virginia and Kentucky Resolves , Origins of U.S. Government: Monroe Doctrine , Civil Rights , Slavery , Slavery: Missouri Compromise , Slavery: Wilmot Proviso , Slavery: Compromise of 1850 , Slavery: Kansas-Nebraska Act , Slavery: Dred Scott v. Sandford , Slavery: "A House Divided" Speech , Slavery: Emancipation Proclamation , From Segregation to Civil Rights , From Segregation to Civil Rights: "The Civil Rights Cases" , From Segregation to Civil Rights: Plessy v. Ferguson , From Segregation to Civil Rights: Letter from Birmingham City Jail , From Segregation to Civil Rights: "I Have a Dream" Speech , From Segregation to Civil Rights: Civil Rights Act of 1964 , From Segregation to Civil Rights: Voting Rights Act of 1965 , From Segregation to Civil Rights: Americans with Disabilities Act of 1990 , Women's Rights , Women's Rights: Seneca Falls Declaration of Sentiments , Women's Rights: Ain't I a Woman? , Women's Rights: Bradwell v. Illinois , Women's Rights: National Organization for Women Statement of Purpose , Native American Rights , Native American Rights: Worcester v. the State of Georgia , Native American Rights: Surrender Speech , Native American Rights: Treaty with Sioux Nation , Native American Rights: My Son, Stop Your Ears , Reflections on Law and Society , Presidential Speeches , Presidential Speeches: George Washington: Farewell Address , Presidential Speeches: Abraham Lincoln: Gettysburg Address , Presidential Speeches: Abraham Lincoln: Second Inaugural Address , Presidential Speeches: Woodrow Wilson: Fourteen Points , Presidential Speeches: Franklin D. Roosevelt: First Inaugural Address , Presidential Speeches: John F. Kennedy: Inaugural Address , Presidential Speeches: Lyndon B. Johnson: Voting Rights Act Address , Presidential Speeches: Ronald Reagan: First Inaugural Address , Presidential Speeches: George W. Bush: Address to Congress, September 20, 2001 , Presidential Speeches: Barack H. Obama: Inaugural Address , Legal Scholarship , Legal Scholarship: Lawyers and Judges , Legal Scholarship: What Shall be Done with the Practice of the Courts? , Legal Scholarship: Contracts , Legal Scholarship: The Path of the Law , Legal Scholarship: Brief for the Defendant in Error, Muller v. Oregon , Legal Scholarship: Mechanical Jurisprudence , Legal Scholarship: The Causes of Popular Dissatisfaction with the Administration of Justice , Legal Scholarship: Some Reflections on the Reading of Statutes , Legal Miscellany , Presidents and Vice Presidents of the United States , Presidential Nominations to the Supreme Court , Time Chart of the Supreme Court , Succession of Supreme Court Justices , U.S. Attorneys General , British Regnal Years., v. 14. Dictionary of Legal Terms , Cases Index , General Index., v. 1. A to Ba , v. 2. Be-Col , v. 3. Com-Dor , v. 4. DOT-Fre , v. 5. Fri-I , v. 6. J-Ma , v. 7. Mc-Pl , v. 8. Po-San , v. 9. Sar-Ten , v. 10. Ter-Z , v. 11. Milestones in the law, Brown to Kelo , v. 12. Milestones in the law, Lawrence to Roe , v. 13. Primary documents , v. 14. Dictionary of legal terms, Cases index, General index.